278LQT5 transgenic rabbits are characterized by increased repolarization instability and arrhythmia susceptibility. (15th July 2014) - Baczko, I; Juhasz, V; Major, P; Kovacs, M; Hornyik, T; Kerekes, A; Hiripi, L; Bosze, ZS; Papp, JGY; Varro, A
Abstract: Purpose: Despite the existence of some in vivo animal proarrhythmia models, the reliable prediction of the proarrhythmic risk associated with novel compounds under development remains unsatisfactory. Therefore, new models with better predictive value for proarrhythmic risk assessment are needed. In this study, we carried out the primary characterization of a new transgenic LQT5 rabbit model recently generated by our group based on the selective overexpression of mutant human KCNE1 gene in the heart. The missense mutation was first identified in a Chinese LQT syndrome family. Methods: The proarrhythmic susceptibility of LQT5 transgenic rabbits was evaluated by administration of the IKr blocker dofetilide (20 μg/kg). In thiopental anesthetized transgenic (TG; n=26) and wild type rabbits (WT; n=27), the ECG was continuously registered using a specialized computer software before, during and following the infusion of dofetilide, and arrhythmia development was also monitored. ECG recordings were evaluated off-line. Results: Conventional ECG parameters characterizing repolarization duration, the QT and frequency corrected QT intervals (QTc), were not different in the two groups at baseline (QT: 146.9 ± 3.18 in WT vs. 145.7 ± 2.87 ms in TG; QTc: 156.8 ± 2.63 in WT vs. 155.6 ± 2.12 ms in TG, all p>0.05). Following the administration of dofetilide, QT and QTc intervals were significantly prolonged in both groups to a similar extent (QTc: 169.4 ± 3.37 in WT and 167.8 ± 3.17 ms in TG). However, the short-term variability of the QT interval, a novel ECG parameter suggested for the better estimation of repolarization temporal instability and proarrhythmic risk, was higher in KCNE1 transgenic rabbits compared to wild type at baseline (4.8 ± 0.26 in TG vs. 2.8 ± 0.15 ms in WT, p<0.05). Following the administration of dofetilide, the incidence of the typically drug induced Torsades des Pointes arrhythmia was significantly higher in transgenic rabbits compared to wild type (77% in TG vs. 51.8% in WT, p<0.05). Conclusions: Our results suggest that KCNE1 transgenic LQT5 rabbits have high susceptibility to drug induced arrhythmias and may represent a model suitable for the more reliable testing of the proarrhythmic potential of new compounds under development.